Effectiveness of Modelling in Stunting Intervention to Improve Teenage Mothers’ Knowledge About Exclusive Breastfeeding - Hatijar; Candra Yanti, Lilis (Journal of Public Health Sciences, 2025)
Stunting remains a persistent public health problem in Indonesia, strongly associated with early marriage, teenage pregnancy, and inadequate breastfeeding practices. Exclusive breastfeeding for the first six months of life is a key strategy for stunting prevention; however, adolescent mothers often face knowledge and experience barriers. This study aimed to evaluate the effectiveness of a modelling-based intervention in improving adolescent mothers’ knowledge of exclusive breastfeeding in Poso Regency, Central Sulawesi. A quasi-experimental one-group pretest–posttest design was applied, involving 31 adolescent mothers recruited through purposive sampling. The intervention consisted of a 60-minute session, including a 30-minute educational video and a 30-minute live demonstration covering the benefits of exclusive breastfeeding, breastfeeding techniques, breast care, and common breastfeeding challenges. Data were collected using a validated questionnaire (Cronbach’s Alpha = 0.612) and analyzed using paired t-tests with a significance level of p < 0.05. Results showed a significant increase in knowledge scores from pretest (mean = 5.81) to posttest (mean = 6.97), with a mean difference of -1.16 (p = 0.003), indicating improved understanding after the intervention. The findings suggest that modelling-based education integrating visual and practical components effectively enhances knowledge among adolescent mothers. Nevertheless, the absence of a control group and the small sample size limit causal inference and generalizability. These results provide preliminary evidence that modelling interventions are potentially useful pending further research in supporting exclusive breastfeeding promotion and stunting prevention programs